Peranan Psikologi Hukum Bagi Penuntut Umum terhadap Penanganan Juvenile Delinquency - Yogi Andiawan Sagita (Lex Renaissance, 2022)
This study aims to provide answers for the two primary questions, namely: first, what is the role of legal psychology for public prosecutors in handling juvenile delinquency? Second, what are the obstacles in using legal psychology for public prosecutors in handling juvenile delinquency cases? The research method is normative juridical which is collaborated with the approache for empirical method. The results of this study are: first, the role of psychology for Public Prosecutors in Juvenile Delinquency cases is to understand the background, factors. Second, classification or classification of Juvenile Delinquency with the study of psychology, namely criminal psychology which is useful for Public Prosecutors in exercising their authority, such as bein a facilitator, mediator, and the process of prosecution as well as implementing decisions and as supervisors in coaching and resocialization. One of the obstacles to legal psychology for public prosecutors in dealing with juvenile delinquency is that not all public prosecutors have legal psychology skills because not all prosecutors receive integrated SPPA education. Not all areas which are the jurisdiction of the Public Prosecutor can provide facilities and infrastructure in law enforcement based on Legal Psychology.Keywords: Public Prosecutor, Legal Psychology, Restorative Justice. AbstrakPenelitian ini bertujuan untuk menjawab dua pertanyaan utama, yakni: pertama, bagaimana peranan psikologi hukum bagi penuntut umum dalam penanganan juvenile delinquency? Kedua, hambatan apa saja dalam penggunaan psikologi hukum bagi penuntut umum dalam penanganan perkara juvenile delinquency? Metode penelitiannya adalah yuridis normatif yang dikolaborasikan dengan penelitian dengan metode pendekatan empirik. Hasil penelitian ini adalah pertama, peranan psikologi bagi Penuntut Umum dalam perkara Juvenile Delinquency adalah guna memahami latar belakang, faktor-faktor. Kedua, pengelompokan atau penggolongan dari Juvenile Delinquency dengan ilmu psikologi yaitu psikologi kriminal yang berguna bagi Penuntut Umum dalam menjalankan wewenangnya yaitu sebagai fasilitator, mediator, proses penuntutan dan melaksanakan putusan sebagai Pengawas dalam pembinaan dan resosialisasi. Hambatan psikologi hukum bagi penuntut umum dalam penanganan kenakalan remaja antara lain: tidak semua Jaksa Penuntut Umum mempunyai kemampuan Psikologi Hukum karena tidak semua jaksa mendapatkan pendidikan SPPA terpadu. Tidak semua daerah yang menjadi wilayah hokum Jaksa Penuntut Umum dapat memberikan sarana dan prasarana didalam penegakan hukum yang didasari oleh Psikologi Hukum. Kata-kata Kunci: Penuntut Umum, Psikologi Hukum, Restorative Justice.